A first-principles study on the bond characteristics in carbon containing Mo, Ag, or Al impurity atoms - Choi, Jung-Hae; Lee, Seung-Cheol; Lee, Kwang-Ryeol (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
The atomic bond characteristics between carbon and metal atoms are investigated by the first-principles calculation using a tetrahedron bond model. Both the charge density distribution of the highest occupied molecular orbital and the partial density of states were examined to reveal the bond characteristics. The chemical bond characteristics between Mo and carbon are nonbonding, which would reduce the bond directionality On the other hand, noble metals such as Ag show antibonding characteristic with carbon. The bond between Al and carbon has ionic characteristics and was found to prefer a two-dimensional configuration. The effect of metallic impurities in carbon materials could be explained from the difference in the atomic bond characteristics. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: ENERGY; FILMS; TI